The conceptual design of a demo-imitation separatorthe model of a plasma mass filter for irradiated oxide uranium fuel - Yuferov, V.B.; Ilichova, V.O.; Katrechko, V.V.; Shariy, S.V.; Svichkar, A.S.; Shvets, M.O.; Tkachov, V.I.; Vinnikov, D.V.; Ozerov, A.N. (Вопросы атомной науки и техники, 2018)
The design of a demo-imitation separator is presented which is the model of a plasma filter for the masses of irradiated oxide uranium fuel. Expected setup productivity is ~15…20 tons/year of the material – imitator, that corresponds to the production of SNF per year in WWER-1000 reactor. A non-radioactive multicomponent mixture of oxides of actinides, lanthanides, zirconium, molybdenum can be used as a working material for research. Depending on the state of the working material, the separator may have a horizontal or vertical position. Представлено конструкцію демонстраційно-імітаційного сепаратора, що є моделлю плазмового фільтра для мас-опроміненого оксидного уранового палива. Очікувана продуктивність установки складає ~ 15…20 тонн на рік матеріалу-імітатора, що відповідає виробленню ВЯП на рік реактора ВВЕР-1000. Як робочий матеріал для дослідження можна використовувати нерадіоактивну багатокомпонентну суміш оксидів актиноїдів, лантаноїдів, цирконію, молібдену. В залежності від стану робочого матеріалу, сепаратор може мати горизонтальне або вертикальне положення. Представлена конструкция демонстрационно-имитационного сепаратора, который является моделью плазменного фильтра для масс-облученного оксидного уранового топлива. Ожидаемая производительность установки составляет ~ 15…20 тонн на год материала-имитатора, что соответствует наработке ОЯТ в год реактора ВВЭР-1000. В качестве рабочего материала для исследования может использоваться нерадиоактивная многокомпонентная смесь оксидов актиноидов, лантаноидов, циркония, молибдена. В зависимости от состояния рабочего материала сепаратор может иметь горизонтальное или вертикальное положение.